Assessing the climate change and its impact on livelihoods of smallholder farmers in Karaga district of Ghana - Alhassan Bawa (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2025)
Agricultural production and food security among smallholder farmers has been threatened as a results of the effect of the changing climate. This study sought to analyse the changing climate and its impact on livelihoods among smallholder rural farmers in the Karaga district of Ghana. The research adopted a mixed-method approach where both quantitative and qualitative data were used. Primary data was obtained from 272 households through interviews, focus group discussions, field observation, and key informant interviews. The findings show that majority of farmers recognize the negative effects of climate change on their livelihoods. Farmers also perceive potential benefits from new technologies such as high-yielding varieties and irrigation that can enhance their well-being. Smallholders also confirmed that the adaptation and mitigation strategies were through indigenous weather forecasting, and bio-insecticides innovations. In the years of crop failure because of climate hazards, smallholder farmers resort to trading, firewood harvesting for sale and charcoal burning as a coping livelihood strategy. The research also reveals that there is no significant differences between gender and adaptation response to the changing climate. The study further reveals that women and children are the most vulnerable during climate-related displacements. In conclusion, the ancient traditional practices of smallholder farmers, such as the use of ‘rain callers’, the use of forest reserves as shrines, indigenous weather forecasting, and the use of bio-insecticide innovation, are still very relevant in adapting to climate variability. The research recommends the promotion of indigenous weather information systems and sustainable agricultural practices to build rural smallholders' capacity to adapt.